Do female and ethnically diverse executives endure inequity in the CEO position or do they benefit from their minority status? An empirical examination - Hill, Aaron D.; Upadhyay, Arun D.; Beekun, Rafik I. (Strategic Management Journal, 2015)
We present competing hypotheses regarding whether gender and ethnic minority CEO s endure inequities resulting in lower compensation and higher likelihood of job exit or benefit from their valuable, rare, and inimitable minority status, resulting in higher compensation and lower likelihood of job exit. Using a longitudinal sample, we find support for the resource‐based hypothesis regarding compensation that suggests CEO s benefit from their minority status to receive higher compensation than white male CEO s receive. However, we also find mixed support for our hypotheses relating CEO minority status to the likelihood of exit. We find that the effects of minority status on likelihood of exit are significantly different for female and ethnic minority CEO s such that the former relationship is negative while the latter is positive . Copyright © 2014 John Wiley & Sons, Ltd.